МУСТАҚИЛ ТАЪЛИМДА WEB ВА ТАЪЛИМ ТЕХНОЛОГИЯЛАРИДАН ҲАМКОРЛИКДА ФОЙДАЛАНИШ ОРҚАЛИ ТАЛАБАЛАРДА ИННОВАЦИОН ҚАРАШЛАРНИ ШАКЛЛАНТИРИШ - Атаджанов, Х. (SCIENCE and SOCIETY, 2020)
The article deals with modern methods of organizing independent work of students in their preparation to use information and communication technologies. The urgency of the problem is due to the requirements of employers to the personal qualities of the modern student. The subject of this paper is the electronic textbook, designed for web 2. 0-based technologies.
Keywords: independent work of students; ways of organizing independent work of students; case of technology; project method; Web2.0 technology; e-learning resources